Internet-based troubleshooting and monitoring system of industrial robots - Rahman, Md. Mozasser; Parnin, Sulleha (2015)
This paper presents a prototype of an industrial robot monitoring system that is remotely control via internet. The use of industrial robot is increasing in small to medium enterprise (SME’s) as low-cost robots are available in market. Productivity can be increase by incorporating robots. The limitations of maintenance and troubleshooting personnel to monitor the robot will always existbecause they are not always being in the robot operation area. Thus, a prototype of a monitoring system was developed and tested in the Robotics laboratory of International Islamic University Malaysia, using Denso robots. The remote monitoring system can monitor the robot condition by a real time video streaming using internet. Arduino microcontroller was used to send the signal to the robot from a computer. This open source software fit the requirement of this project which enable the development to be completed with a low cost budget. The user interface program was created using the Guided User Interface which enables the programmer to monitor the robot from a remote area by using TeamViewer application. A USB camera was also used to see the real time video of the robot. All the subsystem was successfully integrated by Define, Data Gathering and Analysis, Develop, Testing and Improve to accomplish the project goals and at the same time becoming a starting point for further development.